Severe phenotypic spectrum of biallelic mutations in PRRT2 gene. Issue 7 (16th January 2015) - Delcourt, Marion; Riant, Florence; Mancini, Josette; Milh, Mathieu; Navarro, Vincent; Roze, Emmanuel; Humbertclaude, Véronique; Korff, Christian; Des Portes, Vincent; Szepetowski, Pierre; Doummar, Diane; Echenne, Bernard; et al.
Abstract : Background: Heterozygous dominant mutations of PRRT2 have been associated with various types of paroxysmal neurological manifestations, including benign familial infantile convulsions and paroxysmal kinesigenic dyskinesia. The phenotype associated with biallelic mutations is not well understood as few cases have been reported. Methods: PRRT2 screening was performed by Sanger sequencing and quantitative multiplex PCR of short fluorescent fragments. A CGH array was used to characterise the size of the deletion at the 16p11.2 locus. Results: Five patients with homozygous or compound heterozygous deleterious PRRT2 gene mutations are described. These patients differ from those with a single mutation by their overall increased severity: (1) the combination of at least three different forms of paroxysmal neurological disorders within the same patient and persistence of paroxysmal attacks; (2) the occurrence of uncommon prolonged episodes of ataxia; and (3) the association of permanent neurological disorders including learning difficulties in four patients and cerebellar atrophy in 2. Conclusions: Our observations expand the phenotype related to PRRT2 insufficiency, and highlight the complexity of the phenotype associated with biallelic mutations, which represents a severe neurological disease with various paroxysmal disorders and frequent developmental disabilities.